Hegemoni Budaya dalam Tradisi Manaqiban - Bani Sudardi; Afiliasi Ilafi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2017)
This research is to find out how cultural hegemony that occur in manaqiban tradition in Desa Sari Kecamatan Gajak Kabupaten Demak that can affect the outside community by exercising powers that happened. Manaqiban tradition is a ritual performed by the society in which the people of Java and Madura as a tribute to something about it. Manaqiban tradition also conducted in Desa Sari with a time of implementation is on the eve of the sacred. This tradition was carried out as a form in order to honor the founder of the Desa Sari. Manaqiban tradition in the Desa Sari implemented in a tomb of the gentry named Mbah Djomo. This study used a qualitative approach and data sources of gatekeeper Mbah Djomo. The technique used is by collecting data through observation, interviews, and documentation.